Social Media Listening to Understand the Lived Experience of Individuals in Europe With Metastatic Breast Cancer: A Systematic Search and Content Analysis Study - Mazza, Manuelita; Piperis, Maria; Aasaithambi, Sathyaraj; Chauhan, Jyoti; Sagkriotis, Alexandros; Vieira, Claudia (Frontiers in Oncology, 2022)
Background Despite a wealth of real-world data in metastatic breast cancer (mBC), insights into the lived experience are lacking. This study aimed to explore how the lived experience of mBC is described on social media. Methods A predefined search string identified posts relevant to the lived experience of mBC from Twitter, patient forums and blogs, across 14 European countries. The final data set was analyzed using content analysis. Results 76,456 conversations were identified between 1 November 2018 to 30 November 2020. Twitter was the most commonly used social media platform across all 76,456 conversations from the raw data set (n = 61,165; 80%). Automated and manual relevancy checks followed by a final random sampling filter identified 820 conversations for content analysis. The majority of data from the raw data set was generated from the United Kingdom (n = 31,346; 41%). From this final data set, 61% of posts were authored by patients, 15% by friends and/or family members of patients, and 14% by caregivers. A total of 686 conversations described the patient journey (n = 686/820; 84%); 64% of these (n = 439) concerned breast cancer treatment, with approximately 40% of discussions regarding diagnosis and tests (n = 274/686) and less than 20% of discussions surrounding disease management (n = 123/686; 18%). Key themes relating to a lack of effective treatment, prolonged survival and associated quality of life, debilitating consequences of side effects, and the social impacts of living with mBC were identified. Conclusions The findings from this study provided an insight into the lived experience of mBC. While retrospective data collection inherently limits the amount of demographic or clinical information that can be obtained from the population sample, social media listening studies offer training of healthcare professionals in communication, importance of quality of life, organization of healthcare, and even for the design of clinical trials. As new targeted therapies are gradually incorporated into clinical practice, innovative technologies, such as social media listening, have the potential to support regulatory procedures and drug toxicity monitoring, as well as provide the patient voice in the regulation of new and existing medicines.